Predisposition, Pathogenesis, and Management of Fungal Pneumonia - Suriana Dwi Sartika (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2022)
Fungal pneumonia is a lung infection process caused by one or more pathogenic and opportunistic fungi. Fungal pneumonia or pulmonary mycosis that are often reported are aspegillosis, candidosis, cryptococcus, and histoplasmosis. Commonly reported risk factors include fungal colonization, long-term use of broad-spectrum antimicrobials, systemic corticosteroids, cytostatic drugs, and invasive medical devices. Management for fungal pneumonia is antifungal based on the fungal cause, severity, and clinical condition of each patient.